Bioequivalence Study of Modified-Release Gliclazide Tablets in Healthy Volunteers - Rojanasthien, Noppamas (International Scholarly Research Network, 2012)
This study was aimed to investigate bioequivalence of modified-release 30 mg gliclazide tablets in 18 healthy Thai volunteers. A test product, Glycon MR (Siam Bheasach, TH), was compared with a reference product, Diamicron MR (Servier, France). The study was performed under a single-dose, two-treatment, two-period, and two-sequence crossover design in fasted and fed conditions with a washout period of 2 weeks. Blood samples were collected for 72 h after drug administration. Drug plasma concentrations were determined by HPLC with a UV detector. Analysis of pharmacokinetic characteristics was based on a non-compartmental model. The logarithmically transformed data of C(max) and AUCs were analyzed for 90% confidence intervals using ANOVA. The test product gave slightly higher C(max) in both conditions and shorter T(max) in the fed condition. However, there is no significant difference in pharmacokinetic characteristics between both products under fasted and fed conditions. Effect of food was not significantly observed. The 90% confidence intervals were within the acceptance criteria of 0.80–1.25 regardless of the food effect, indicating bioequivalence between the two products on the rate and extent of gliclazide MR absorption without regard to meals.